2013
DOI: 10.1063/1.4819272
|View full text |Cite
|
Sign up to set email alerts
|

Gallium nitride nanowires by maskless hot phosphoric wet etching

Abstract: We demonstrate gallium nitride (GaN) nanowires formation by controlling the selective and anisotropic etching of N-polar GaN in hot phosphoric acid. Nanowires of ∼109/cm,2 total height of ∼400 nm, and diameters of 170–200 nm were obtained. These nanowires have both non-polar {11¯00}/ {112¯0} and semi-polar {1011¯} facets. X–Ray Diffraction characterization shows that screw dislocations are primarily responsible for preferential etching to create nanowires. Indium gallium nitride multi-quantum wells (MQWs) grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…From SEM analysis of the as-etched pyramidal nanowires, the estimated angle of the top semipolar facet was 12°from the [0001] c-direction, which was consistent across different nanowires and at different etch times. Previously, it has been reported that H 3 PO 4 etches N-face ( ¯) 0001 GaN into dodecagonal pyramids [59][60][61][62] and etches hexagonal pits at defect sites in Ga-face ( ) 0001 GaN [61,[63][64][65][66]. Thus, the H 3 PO 4 etch for GaN can be considered crystallographic in nature, much like the KOH-based etch, but with semipolar rather than nonpolar planes being exposed.…”
Section: Gan Nanowires Etched In H 3 Pomentioning
confidence: 99%
“…From SEM analysis of the as-etched pyramidal nanowires, the estimated angle of the top semipolar facet was 12°from the [0001] c-direction, which was consistent across different nanowires and at different etch times. Previously, it has been reported that H 3 PO 4 etches N-face ( ¯) 0001 GaN into dodecagonal pyramids [59][60][61][62] and etches hexagonal pits at defect sites in Ga-face ( ) 0001 GaN [61,[63][64][65][66]. Thus, the H 3 PO 4 etch for GaN can be considered crystallographic in nature, much like the KOH-based etch, but with semipolar rather than nonpolar planes being exposed.…”
Section: Gan Nanowires Etched In H 3 Pomentioning
confidence: 99%
“…Several chemical solutions have been previously demonstrated for wet etching of GaN, including KOH, H 3 PO 4 , and tetramethylammonium hydroxide (TMAH), [7][8][9] although in general these etches require elevated temperatures and high concentrations in order to produce useful etch rates, and the resulting surface morphology and etch performance is often poor for device applications. Photoelectrochemical (PEC) etching offers significant advantages; the use of optical illumination to generate electron-hole pairs near the surface during the etch process allows for additional flexibility such as dopant-and bandgap-selective etching.…”
Section: Introductionmentioning
confidence: 99%
“…A flexible GaN membrane platform on a silicon wafer developed by eutectic bonding and a laser lift-off process offers flexibility for the stable and reliable design of various pixel shapes and related manufacturing processes. Flexible GaN has also been developed using other techniques such as the selective anisotropic etching of N-polar GaN in hot phosphoric acid [ 97 ]. However, there are few reports on the preparation of flexible GaN via electrochemical etching methods.…”
Section: Synthesis Methods For (In)gan Nanostructuresmentioning
confidence: 99%